(untitled) (Journal of Bangladesh Academy of Sciences, 2025)
This study documents a case of tail bifurcation in the Tokay Gecko (Gecko gecko) observed in Satchari National Park, Bangladesh. While generally abundant, this instance underscores limited research on the species in the region. The unusual tail morphology and loss of digits on a hindlimb suggest predation and its potential adverse effects on the gecko’s fitness, warranting further investigation. J. Bangladesh Acad. Sci. 49(1); 153-156: June 2025